The Improvement of Organizational Commitment through The Strengthening Personality Traits, Transformational Leadership, Organizational Culture, and Job Satisfaction - Yuliana, Tiarma Ika; Hardhienata, Soewarto; Laihad, Griet Helena (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The purpose of this research is to find the strategies and ways to improve the organizational commitment of private vocational school teachers, namely by strengthening the independent variables that have a positive effect on teacher commitment. These variables are Personality Traits, Transformational Leadership. Organizational Culture, and Job Satisfaction. The optimal solution of this research can be used as a recommendation to related parties, namely teachers, principals, school supervisors, school management institutions and education agencies. The method of this research is quantitative method by using survey methods, path analysis techniques and SITOREM analysis, those are used to indicators to determine optimal solutions in improving teacher commitment. The research was conducted on permanent foundation teachers (GTY) of private Vocational High Schools (SMK) in East Jakarta with a population of 381 teachers, with a sample of 195 teachers calculated using the Taro Yamane formula. The results of this research show there is a positive direct an significant effect of personality traits, transformational leadership, organizational culture and job satisfaction variables on Organizational Commitment; there is a positive direct and significant effect of personality traits, transformational leadership and organizational culture on Organizational Commitment; there is a positive indirect effect of personality traits, transformational leadership, organizational culture, on Organizational Commitment through Job Satisfaction.